Язык и познание. Диаграмматическая иконичность в сказке Алексея Толстого Золотой ключик, или приключения Буратино и ее польском переводе - Rycielska, Beata (Studia Rossica Posnaniensia, 2019)
The paper refers to one of the types of diagrammatic iconicity singled out on the basis of the similarity of the form of the sign in a sequential order to the content. The text discusses coordinate and subordinate phrases which embody the principle. The paper emphasizes the differences existing between them in terms of the freedom of order of structural components. Further, it compares the source text and the target text applying the sequential order principle as tertium comparationis.